Polish State Railways in 1945–1989 – A Research Contribution - Keller, Dawid (Studia Historiae Oeconomicae, 2021)
In the history of Poland after 1945, the functioning of the railway was one of the most important elements of everyday life – great migrations, modernity, commuting to work or holidays, military or employment. The largest transport in history was recorded by the state carrier at the end of the seventies. In reality, however, the activity of PKP was paid for by numerous compromises – outdated rolling stock, organizational structure and network in fact reflecting the beginning of the 20th century, the pursuit of electrification of almost all sections with a limited degree of motorization, mass transport and the abandonment of many potential customers. The aim of the article is to summarize the state of research and indicate questions that will allow to answer the question posed in the title. The inspiration came from the thesis of M. Jarząbek, expressed a few years ago, that the railway in this epoch from a symbol of modernity became an unwanted choice out of necessity.